Response surface optimization of microwave-assisted high performance liquid chromatography-inductively coupled plasma mass spectrometry for determining eight arsenic species in marine fish - Xiao-qiong Wu; Guo-Ying Zhu; Zhong-wen Chen; Miao-hua Ge (All Life)
This study optimized microwave-assisted extraction conditions for determining eight arsenic species in marine fish using High-Performance Liquid Chromatography-Inductively Coupled Plasma Mass Spectrometry. Response surface methodology was applied to optimize four key parameters: methanol volume fraction, extraction time, extraction temperature, and solid–liquid ratio. A second-order polynomial regression model was developed using single-factor experiments and Box–Behnken design, and the accuracy of the predictive conditions was verified in six types of marine fish samples. The optimized extraction conditions were: 30% methanol, 32 minutes extraction time, 85 °C extraction temperature, and a solid–liquid ratio of 1:20 (g/mL). Under these conditions, the predicted arsenic speciation content in saury was 277.05 µg/kg, with a measured value of 297.43 µg/kg (6.90% deviation), and spiked recovery rates ranging from 82.1% to 103.2%. The total arsenic speciation in six marine fish species ranged from 300.69 to 2,541.84 µg/kg, with extraction efficiencies between 85.4% and 92.4%. The optimized extraction method significantly improved detection efficiency compared to traditional ultrasonic extraction techniques, demonstrating its suitability for arsenic speciation analysis in marine fish and contributing to a better understanding of arsenic distribution in marine food products.